PEMILIHAN UNIVERSITAS FAVORIT SISWA MADRASAH ALIYAH AL-ISLAMIYAH DI JAKARTA BARAT DENGAN MENGGUNAKAN METODE MARKOV CHAIN - Adi Teguh Suprapto; Aris Setiyarini; Haryadi Sarjono (Universitas Bunda Mulia, 2017)
The purpose of this study was to determine the amount of transfer of interest at class XII student at Madrasah Aliyah Al-Islamiyah in West Jakarta to five favorite namely UIN, BINUS, UNJ, UI and UMN in the next period and to discover the source of reference selection and assessment of student on the fifth university. Sample consists of 39 class XII student at Madrasah Aliyah Al-Islamiyah in West Jakarta, with the methods and type of survey of survey research is descriptive research. The result is a prediction of the five university in order in the next period of (0.5135, 0.1008, 0.2077, 0.078, 0.1) and the selection of a reference source that is 0.62 of brand image, 0.583 of the promotional events, 0.582 from friends and 0.54 of the university security. Largest market share held by UIN enthusiasts of 51%, while the smallest market share owned by UI enthusiasts is equal to 8%.Keywords: Markov Chain, Favorite, Madrasah Aliyah Al-Islamiyah (MA), West Jakarta, University